«Non querades seguir esta carrera que es (de) ufana et llena de vanidat» - Zieliński, Andrzej (Verba hispanica, 2021)
The purpose of this paper is to delve into the origin and the discursive trajectory of the deontic modal value expressed by the Spanish verbal periphrasis querer ‘to want’ + infinitive. Although it is documented for the first time in Castilian texts of the thirteenth century, its late use – in comparison with oth-er modal and temporal meanings that the verbal construction acquired – seems to draw from Latin sources in which NOLI / NOLITE (< NON VOLO ‘I do not want’) was used with a moralizing sense. Thus, by means of an analysis based on data extracted from CORDE, the author tries to elucidate (i) what is its evolutionary path and (ii) which discursive contexts favour the semantic change motivated by the interference of the Latin model. The hypothesis that the author aims to demonstrate is that the emergence of the new deontic value, emanating from the medieval construction querer ‘to want’ + infinitive, arises from the mechanism of semantic calque used by authors influenced by Latin texts. Therefore, the contact-induced grammaticalization of the construction non quieras / non querades + infinitive derives from the original meaning of ‘intention’, arising from the construction querer ‘to want’ + infinitive, where the strong disposition of the agentive subject to achieve the dynamic activity takes over, in the eyes of the speaker, the performative content. The effect is that such an intervention appeals to the will of the agentive subject in order to keep them from carrying out the action that was originally intended to be performed.
Keywords: deontic modality; deontična naklonskost; discursive traditions; diskurzivne tradicije; gramatikalizacija; grammaticalization; interference